HKUST-1-Catalyzed Chan–Evans–Lam C–O Coupling Under Mild Conditions with Catalyst Reusability - Sidik, Muhamad R. S.; Kurnia, Irwan; Permana, Yessi; Arrozi, Ubed S.F.; Ciptonugroho, Wirawan; Lestari, Witri Wahyu; Budiman, Yudha Prawira (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
The Chan–Evans–Lam coupling refers to a valuable method for constructing C–O and C–N bonds under mild conditions. Nevertheless, the development of efficient and reusable heterogeneous catalysts remains limited. In this study, we investigated copper-based metal–organic frameworks as catalysts for C–O bond formation between 4-methoxyphenylboronic acid and phenol. The study revealed that HKUST-1 exhibited a significant enhancement in performance when compared to Cu-BDC, yielding up to 86% at room temperature and demonstrating superior accessibility of Cu2+ active sites. A systematic optimization of reaction parameters identified NEt3 as the most effective base, DCM as the optimal solvent, and a mild temperature increase to 40 °C as the key factor enabling a maximum yield of 94%. Studies on recyclability demonstrated that HKUST-1 exhibited high catalytic performance over multiple cycles without significant structural degradation, as confirmed by PXRD analysis. Overall, this work highlights HKUST-1 as an efficient, robust, and reusable heterogeneous catalyst for Chan–Evans–Lam C–O coupling, thus demonstrating its potential for sustainable synthetic applications.